Protein Dynamics in Cytosolic DNA-Sensing Antiviral Innate Immune Signaling Pathways - Zheng, Chunfu (Frontiers in Immunology, 2020)
Antiviral innate immunity works as the first line of host defense against viral infection. Pattern recognition receptors (PRRs) and adaptor proteins involved in the innate immune signaling pathways play critical roles in controlling viral infections via the induction of type I interferon and its downstream interferon-stimulated genes. Dynamic changes of adaptor proteins contribute to precise regulation of the activation and shut-off of signaling transduction. While it’s still a mass of complex process in dynamic changes of various protein from host and viruses. In this review, we will summarize the recent progresses on the trafficking patterns and conformational transitions of such adaptors that are involved in the antiviral innate immune signaling pathway during viral DNA sensing. Meanwhile, we aim to dissect the relationships between protein dynamics and DNA sensing antiviral innate immune responses, which will reveal the underlying mechanisms on how to control proteins activity and maintain cell homeostasis. With comprehensive revealing of protein dynamic in cytosolic DNA sensing antiviral innate immune signaling pathway, we will be able to gain potential new targets for the therapies of certain autoimmune diseases.